2017
DOI: 10.1121/1.4995998
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic enhancement of Mandarin vowels and tones: Infant-directed speech and Lombard speech

Abstract: Speech units are reported to be hyperarticulated in both infant-directed speech (IDS) and Lombard speech. Since these two registers have typically been studied separately, it is unclear if the same speech units are hyperarticulated in the same manner between these registers. The aim of the present study is to compare the effect of register on vowel and tone modification in the tonal language Mandarin Chinese. Vowel and tone productions were produced by 15 Mandarin-speaking mothers during interactions with thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 43 publications
4
41
0
Order By: Relevance
“…The results showed that the median F0 was higher and F0 excursions were larger in IDS compared to ADS at both ages. Vowels in Mandarin Chinese IDS are hyperarticulated (Liu, Tsao, & Kuhl, 2009;Tang, Xu Rattanasone, Yuen, & Demuth, 2017), but vowels in Dutch IDS show hypoarticulation instead (Benders, 2013). In addition, lexical tones in Mandarin Chinese IDS are hyperarticulated (Han, de Jong, & Kager, 2018a;Tang et al, 2017).…”
Section: Pitch Properties Of Ids Specific To Word Learning Contextsmentioning
confidence: 96%
“…The results showed that the median F0 was higher and F0 excursions were larger in IDS compared to ADS at both ages. Vowels in Mandarin Chinese IDS are hyperarticulated (Liu, Tsao, & Kuhl, 2009;Tang, Xu Rattanasone, Yuen, & Demuth, 2017), but vowels in Dutch IDS show hypoarticulation instead (Benders, 2013). In addition, lexical tones in Mandarin Chinese IDS are hyperarticulated (Han, de Jong, & Kager, 2018a;Tang et al, 2017).…”
Section: Pitch Properties Of Ids Specific To Word Learning Contextsmentioning
confidence: 96%
“…However, it should be noted that this line of research typically relies on a rather small set of stimuli due to the practicalities of testing children. For example, Kuhl et al (1997) used one target word per vowel; Liu et al (2007) had twelve syllables for four tones, but they only included “the first two clear tokens of each target word”; Tang et al (2017) also used one syllable for each tone. Even though there has been some agreement on the salience of tone hyperarticulation in the first year of life, it has not been established that tone hyperarticulation is present across the board.…”
Section: Discussionmentioning
confidence: 99%
“…Second, enhancement of tonal contrasts is a possible indicator of tone hyperarticulation in IDS. Such enhancement can be measured by comparing the pitch differences between tone pairs in ADS and IDS, or indicated by a larger tone triangle in IDS (e.g., Tang et al, 2017 , to review later). To date, only a handful of studies have looked at lexical tones in IDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infants' environments are rich in affective content, as infant-directed speech (IDS) is characterized by exaggerated pitch contours reflecting “free vocal expression of emotion” (Trainor et al, 2000 ), which attracts infants' attention (Cooper and Aslin, 1990 ; Werker et al, 1994 ), yet does not a priori facilitate tone acquisition, as it may partially obscure contrastive shapes of tones (Papoušek and Hwang, 1991 ; Kitamura et al, 2002 ). Pitch exaggeration in IDS may be partly compensated by tonal hyper-articulation (Liu et al, 2007 ; Xu Rattanasone et al, 2013 ; Tang et al, 2017 ), yet to what extent precisely is an open issue. In order to facilitate disaggregation of referential and affective pitch, young infants may draw on their ability to recognize vocal and visual expression of affect.…”
mentioning
confidence: 99%